Viral Marketing by Generation Z for Horror Movie Trailers: The Role of Affective and Cognitive Responses and Audience Behaviour - Clorinda, Michelle; Handayani, Yuliasti Ika; Wulani, Fenika (Indonesian Management and Accounting Research, 2026)
This study examines the effect of affective and cognitive responses on viral marketing mediated by Generation Z audience behavior toward horror movie trailers. Movie trailers are one of the things that can attract the attention of the audience, such as feelings of curiosity to watch the horror movie trailer. Positive feelings can make someone intend to share horror movie trailers with others on social media, but horror movie trailers do not always succeed in creating viral marketing.   We used a purposive sampling technique and distributed questionnaires to 104 respondents who had watched horror movie trailers at least once in the last 6 months. Data analysis was conducted using partial least square (PLS) on the Smart-PLS 4.0 software. The results of this study indicate that cognitive response has a positive effect on viral marketing. However, affective response affects viral marketing only through audience behavior. In addition, our study finds that audience behavior mediates the effect of cognitive response on the viral marketing of horror movie trailers.